53.8k views
3 votes
Help me asap! I will give you marks

Help me asap! I will give you marks-example-1
User JJS
by
4.7k points

1 Answer

4 votes

Recall the binomial theorem.


(a+b)^n = \displaystyle \sum_(k=0)^n \binom nk a^(n-k) b^k

1. The binomial expansion of
\left(1+\frac x3\right)^7 is


\left(1 + \frac x3\right)^7 = \displaystyle\sum_(k=0)^7 \binom 7k 1^(7-k) \left(\frac x3\right)^k = \sum_(k=0)^7 \binom 7k (x^k)/(3^k)

Observe that


k = 1 \implies \dbinom 71 \left(\frac x3\right)^1 = \frac73 x


k = 2 \implies \dbinom 72 \left(\frac x3\right)^2 = \frac73 x^2

When we multiply these by
8-9x,


8 and
\frac73 x^2 combine to make
\frac{56}3 x^2


-9x and
\frac73 x combine to make
-\frac{63}3 x^2 = -21x^2

and the sum of these terms is


\frac{56}3 x^2 - 21x^2 = \boxed{-\frac73 x^2}

2. The binomial expansion is


\left(2a - \frac b2\right)^8 = \displaystyle \sum_(k=0)^8 \binom 8k (2a)^(8-k) \left(-\frac b2\right)^k = \sum_(k=0)^8 \binom 8k 2^(8-2k) a^(8-k) b^k

We get the
a^6b^2 term when
k=2 :


k=2 \implies \dbinom 82 2^(8-2\cdot2) a^(8-2) b^2 = 28 \cdot2^4 a^6 b^2 = \boxed{448} \, a^6b^2

User MostafaMV
by
5.5k points